2022
DOI: 10.3390/land11070968
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Environment Effects of Built-Up Land Expansion in Shijiazhuang

Abstract: Exploring the thermal environment effects of built-up land expansion can lay a firm foundation for urban planning and design. This study revealed the spatiotemporal dynamic characteristics of built-up land and heat island center points in Shijiazhuang using land-use/land-cover data and land surface temperature (LST) products from 1996 to 2019, and the response mechanism between the percentage of built-up land (PLAND) and LST with the grid sampling method and statistical analysis. Results indicated that heat is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Ecological spaces such as green areas and water bodies have a cooling effect in cities, known as the cool island effect. The study found that the intensity of the cool island effect increases with the increase in the proportion of ecological space area, like previous research findings [15,23,35,36]. However, this study goes beyond the previous research focus on a single land cover type in relation to the heat island problem and instead explores the long-term spatial pattern evolution of the three ecological spaces in Beijing and its impact on the dynamic distribution of surface heat environment from the perspective of land function.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Ecological spaces such as green areas and water bodies have a cooling effect in cities, known as the cool island effect. The study found that the intensity of the cool island effect increases with the increase in the proportion of ecological space area, like previous research findings [15,23,35,36]. However, this study goes beyond the previous research focus on a single land cover type in relation to the heat island problem and instead explores the long-term spatial pattern evolution of the three ecological spaces in Beijing and its impact on the dynamic distribution of surface heat environment from the perspective of land function.…”
Section: Discussionsupporting
confidence: 62%
“…However, the above-mentioned studies generally provide limited information on the response mechanisms between PLAND indices and LST for various types of spaces, and it is of special significance to analyze the impact of PLES expansions on the urban surface thermal environment based on grids [21,22]. For example, Chen et al proposed a 35% built-up PLAND index to split the thermal environment effect of the construction land expansion in Wu'an City by grid sampling statistics [22], and Qin et al derived a 55-60% PLAND index of the built-up land within the grid to split the thermal environment effect in Shijiazhuang City by a 990 m × 990 m grid analysis [23].…”
Section: Introductionmentioning
confidence: 99%